Parasite a graphic novel in storyboards - Bong, Jun ho 1969- (Grand Central Publishing, 2020)
"In hundreds of mesmerizing illustrations, PARASITE: A Graphic Novel in Storyboards is a behind-the-scenes glimpse at the making of one of the best films in years and a brand-new way to experience a global phenomenon. Drawn by Bong Joon Ho himself before the filming of the Palme d'Or Award-winning, Golden Globe(R)-nominated film, these illustrations, accompanied by every line of dialog in the movie, capture the story in its entirety. Director Bong has also provided a foreword which takes the reader even deeper into the creative process which gave rise to the stunning cinematic achievement of PARASITE. Director Bong's illustrations share the illuminating power of his writing and directing. The result is a gorgeous, riveting read and a fresh look at the vertiginous delights and surprises of Bong Joon Ho's deeply affecting, genre-defying story."--Provided by publisher
Keywords: Dysfunctional families / Korea (South) / Comic books, strips, etc; Swindlers and swindling / Comic books, strips, etc; Dysfunctional families; Swindlers and swindling; Korea (South); Comic books, strips, etc; Graphic novels; Drehbuch